PENGEMBANGAN MODEL BERMAIN SEPAK BOLA MELALUI PENDEKATAN LINGKUNGAN PEPOHONAN PADA SISWA KELAS V SD NEGERI 02 BLUNGUN KECAMATAN JEPON KABUPATEN BLORA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The background of this research is the lack of development of learning models penjasorkes realm. The problem in this study is how the game of football modified form corresponding to fifth grade students Elementary School 02 Blungun Jepon District regency Blora. The method of research is the development of a model refers to the development of Borg & Gall has been modified. Data collection was done using expert evaluation sheet (one expert and one expert penjas learning). The data analysis technique used is descriptive percentage to reveal aspects of psychomotor, cognitive, and affective student after using the product. From the test results obtained by the expert evaluation data, expert penjas 82,5% (good), a Learning 85% (very good), a small test group 89% (good), and a large group trial 96% (very good). Based on the results of research and discussion, it can be concluded that the game of football trees effective, so it can be applied as a model of learning in the learning penjasorkes. Expected for elementary school teachers penjasorkes 02 Blungun able to use the product models net live football trees games in the learning process penjasorkes